Expressions of mRNA for innate immunity‐associated functional molecules in urinary sediment in immunoglobulin A nephropathy. (December 2015) - Tsuruga, Kazushi; Aizawa, Tomomi; Watanabe, Shojiro; Tsugawa, Koji; Yoshida, Hidemi; Imaizumi, Tadaatsu; Ito, Etsuro; Tanaka, Hiroshi
Abstract: Aim: It has been reported that the innate immune system plays a pivotal role in the pathogenesis of immunoglobulin A nephropathy (IgAN). To explore non‐invasive monitoring of disease activity in children with IgAN, we examined whether expressions of mRNA for innate immunity‐associated functional molecules: CC ligand chemokine 5 (CCL5), fractalkine/CX3CL1, interferon‐γ‐induced protein 10 (IP‐10), monocyte chemoattractant protein 1 (MCP‐1), retinoic acid‐inducible gene‐I (RIG‐I), and toll‐like receptor 3 (TLR3) in urinary sediment from patients with IgAN correlate with histologic parameters. Methods: Twenty consecutive children with IgAN and four children with thin basement membrane disease (serving as a non‐inflammatory control) were enrolled in this pilot study. Urinary mRNA expressions of target genes were examined real‐time quantitative polymerase chain reaction. Results: The expressions of CCL5, fractalkine and RIG‐I were significantly increased in IgAN (all P < 0.05). Although no significant correlation was observed between mRNA expressions of these three molecules and clinical parameters, such as levels of urinary protein excretion, degrees of occult blood in urine and serum albumin, the expression of fractalkine was significantly correlated with the histological activity index ( P = 0.022) and the chronicity index ( P = 0.005). Furthermore, intense glomerular immune activity of fractalkine was observed in biopsy specimens in patients with moderately to severe proliferative IgAN. Conclusion: Regional expression of fractalkine may be involved in the pathogenesis of childhood IgAN. Although our present findings remain preliminary, measurement of mRNA expression of fractalkine in urinary sediment could be used as a non‐invasive method for predicting histologic severity in IgAN in children. Further studies of this issue are needed. Summary at a Glance: In this article, the authors measured the urinary mRNA levels of several innate immunity associated functional molecules in paediatric IgAN patients and demonstrated that fractalkine was significantly correlated with the histological activity index and the chronicity index. They concluded that measurement of mRNA expression of fractalkine in urinary sediment could use as a non‐invasive method for predicting histologic severity in IgAN in children.